Feasibility of Indigenous Peoples Protection Regulations: A Cost-Benefit Analysis Study on Indigenous Peoples' Academic Manuscripts - Aulia Ulfa Septiryani; Indri Jasinta (Universitas Sriwijaya, 2026)
Indigenous legal communities are part of Indonesian society and have been constitutionally recognised through Article 18B paragraph (2) and Article 28I paragraph (3) of the 1945 Constitution of the Republic of Indonesia. However, the absence of a specific law governing indigenous communities means that regulations remain scattered across sectoral regulations, creating legal uncertainty in the recognition of indigenous territories, land rights, and natural resource management. This study aims to examine the feasibility of regulations to protect indigenous communities by evaluating the Academic Draft of the Indigenous Communities Bill against legislative-formation standards and measuring the policy's feasibility using the Cost-Benefit Analysis (CBA) approach. The research method used is normative legal research, employing a statutory-regulatory approach and analysis of legal documents and secondary data. The results of the study indicate that the Academic Draft of the Indigenous Communities Bill has a strong philosophical, sociological, and juridical basis, but still requires strengthening in terms of empirical data, harmonisation of sectoral regulations, and implementation mechanisms to protect indigenous communities. The novelty of this research lies in the use of a Cost-Benefit Analysis approach to complement normative legal studies, enabling the feasibility of establishing regulations to be assessed not only from a legal perspective but also from economic, social, and environmental perspectives. The CBA results indicate that the benefits of establishing regulations to protect indigenous peoples outweigh the implementation costs, making the Indigenous Peoples Bill worthy of development as a sustainable legal instrument for their protection.